Variation and contact time of protective surface coating on fluoride release and recharge from glass ionomer restoration - AL-Dabbagh, Aya Thanoon; AL-Naimi, Raya Jasim (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Glass ionomer cement (GIC) is an effective restorative material known for its ability to release and recharge fluoride over an extended period. The application of fluoride-containing varnish and acidulated phosphate fluoride (APF) gel can substantially enhance the fluoride release and recharge properties of GIC. These additional treatments provide an extra source of fluoride, contributing to the long-term protection and strengthening of teeth. Purpose: This study aims to investigate the fluoride release and rechargeability of a tooth-colored restorative material (glass ionomer) over different time periods following the application of fluoride varnish (F varnish) and APF gel. Methods: Seventy-two specimens were prepared and divided into three groups, each further categorized into four subgroups based on the type and duration of fluoride application. Fluoride release was measured at 24 hours, 1 week, and 1 month, while fluoride recharge was evaluated after the application of F varnish and APF gel. Results: There was no significant difference in fluoride release between 24 hours and 1 week, but a significant decrease was observed after 1 month. The highest fluoride release occurred at 24 hours, while the lowest was recorded at 1 month. After fluoride recharge, there was a significant increase in fluoride release. Conclusion: Fluoride release from glass ionomer restorations was highest at 24 hours, and the rechargeability was greater with a 24-hour F varnish application compared with 12 hours. APF gel demonstrated higher fluoride release than F varnish, and prolonged contact time between the restorative material and the recharging agent resulted in greater fluoride uptake.